2009
DOI: 10.5194/hess-13-1635-2009
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the Lin's and Host hydropedological models to predict grape yield and wine quality

Abstract: Abstract. The adoption of precision agriculture in viticulture could be greatly enhanced by the diffusion of straightforward and easy to be applied hydropedological models, able to predict the spatial variability of available soil water. The Lin's and Host hydropedological models were applied to standard soil series descriptions and hillslope position, to predict the distribution of hydrological functional units in two vineyard and their relevance for grape yield and wine quality. A threeyears trial was carrie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Roots are not uniformly distributed in the soil, water availability is heterogeneous in space and time, and such heterogeneity affects plant physiology at the whole-plant level. Finally it has been observed that plants, including grapevines (Costantini et al, 2009), can absorb water at lower levels than the theoretical wilting point (i.e. −15 kPa).…”
Section: Assessing the Soil Water Availability To Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Roots are not uniformly distributed in the soil, water availability is heterogeneous in space and time, and such heterogeneity affects plant physiology at the whole-plant level. Finally it has been observed that plants, including grapevines (Costantini et al, 2009), can absorb water at lower levels than the theoretical wilting point (i.e. −15 kPa).…”
Section: Assessing the Soil Water Availability To Plantsmentioning
confidence: 99%
“…Grapes also ripen faster on clayey soils. In Tuscany, moderately saline soils have been shown to produce the best wines (as evaluated by a sensory panel) even if water is not limited, probably because the lower osmotic potential induces a moderate water deficit, as measured by δ 13 C (Costantini et al, 2009(Costantini et al, , 2010. Soil texture modifies the plant's response to drought, as shown by Tramontini et al (2012), who studied the effect of texture on grapevine physiology in neighbouring soils during the same vintage.…”
Section: Plant and Soil Water Relationships In Terroirmentioning
confidence: 99%
“…In other respects, soil compaction caused by tillage operations and machine traffic in vineyards is also likely to have effects on vine growth and grape production (Legros et al, 1998;Coulouma et al, 2006;Lagacherie et al, 2006). As a result, detailed characterization of the spatial variation of soil hydrogeophysical properties is of prime importance for the definition of optimal vineyard management practices (Bramley and Hamilton, 2007;van Leeuwen et al, 2008;Costantini et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…In the Douro, heat and water stress at critical periods of the growing season represent a major constraint for wine quality and production (Hardie and Considine , Moutinho‐Pereira et al ). Other important forcing factors remain invariant between years, such as soils, cultural practices and cultivars grown (Hedberg and Raison , Fidelibus et al , Costantini et al , Renouf et al , Kamiloglu , Tardaguila et al , Fraga et al ). The relevance of climate and weather conditions for wine production in the DDR is highlighted by the existence of a ranking system for vineyard plots (from A, the best class, to F), in which climate has a strong weight.…”
Section: Introductionmentioning
confidence: 99%